2018
DOI: 10.1080/01443615.2017.1370579
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection during pregnancy: current concepts on a common multifaceted problem

Abstract: Urinary tract infections (UTIs) are the most common bacterial infection in pregnancy, increasing the risk of maternal and neonatal morbidity and mortality. Urinary tract infections may present as asymptomatic bacteriuria, acute cystitis or pyelonephritis. Escherichia coli is the most common pathogen associated with both symptomatic and asymptomatic bacteriuria. If asymptomatic bacteriuria is untreated, up to 30% of mothers develop acute pyelonephritis, with an increased risk of multiple maternal and neonatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
4
29

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 49 publications
4
103
4
29
Order By: Relevance
“…The decidua basalis is the maternal fetal immunologic interface and it has been shown that local inflammation in area can lead to acute atherosis and poor trophoblast invasion. Additionally, studies have shown that women with asymptomatic bacteriuria, urinary tract infection, and chronic pyelonephritis are at increased risk for preeclampsia (168,169). Another study by den Hollander et al found that Helicobacter pylori, as a cause of chronic inflammatory conditions, is associated with an increased risk of PEC (170).…”
Section: Hypothesis For How Altered Microbiome Affects Pec and Iugrmentioning
confidence: 99%
“…The decidua basalis is the maternal fetal immunologic interface and it has been shown that local inflammation in area can lead to acute atherosis and poor trophoblast invasion. Additionally, studies have shown that women with asymptomatic bacteriuria, urinary tract infection, and chronic pyelonephritis are at increased risk for preeclampsia (168,169). Another study by den Hollander et al found that Helicobacter pylori, as a cause of chronic inflammatory conditions, is associated with an increased risk of PEC (170).…”
Section: Hypothesis For How Altered Microbiome Affects Pec and Iugrmentioning
confidence: 99%
“…The risk of spontaneous preterm birth increases significantly with the number of risk factors for prematurity [12]. In our group of patients, we observed that in the two cases where birth occurred before 28 weeks there were multiple factors related to prematurity such as polyhydramnios, hypothyroidism, first-trimester bleeding, bacterial vaginosis, urinary tract infection, amniotic fluid sludge, cervical funneling and/or fetal malformations [13] [14] [15].…”
Section: Resultsmentioning
confidence: 99%
“…Gebelik esnasında oluşan bazı anatomik, hormonal ve fonksiyonel değişiklikler nedeni ile üriner sistem enfeksiyonuna (ÜSE) yatkınlık artmakta ve bu hastaların uygun şekilde tedavi edilmesi önerilmektedir (1,2). Gebelerdeki ÜSE komplike olarak kabul edilmekte ve uygun şekilde tedavi edilmeyen ÜSE ise preterm eylem, erken membran rüptürü, koryoamniyonitis, neonatal enfeksiyon ve düşük doğum ağırlığı gibi daha ciddi bazı sonuçlara yol açabilmektedir (3). ÜSE için risk faktörleri mevcut olan gebelerin ilk başvurusunda mutlaka idrar kültür-antibiyogram çalışması önerilmektedir (4).…”
Section: Introductionunclassified